Habitual Exploited Business Model Pillars From 1996-2010 - Sabir, M. Suleman; Waheed, Usman (Journal of Asian Business Strategy, 2014)
Although there is no widely agreed upon definition and composition of the business model concept, it is evident from the continued presence of the term in both scholarly and broader business literature, that managers and researchers alike find it a useful descriptive and analytical construct. This paper reviews research in the field of business models from 1996 to 2010. Electronic database searches of scholarly journals spanning 1996 when the term business model first appeared in multiple publications to 2010 reveals 62 articles that use the business model components. We identified twenty-eight blocks used in construction of business model and found each blocks importance percentage (%) in construction of business model through implication of dichotomy analysis. The concluded that three have to ask before design a business model. This study may be further explored through proving of this study results on empirical basis.